Review on different experimental techniques developed for recording force-deformation behaviour of soft tissues; with a view to surgery simulation applications. (19th May 2017) - Afshari, Elnaz; Rostami, Mostafa; Farahmand, Farzam
Abstract: Different experimental techniques which have been developed to obtain data related to force-deformation behaviour of soft tissues play an important role in realistically simulating surgery processes as well as medical diagnoses and minimally invasive procedures. Indeed, an adequate quantitative description of soft-tissue-mechanical-behaviour requires high-quality experimental data to be obtained and analysed. In this review article we will first scan the motivations and basic technical issues on surgery simulation. Then, we will concentrate on different experimental techniques developed for recording force-deformation (stress-strain) behaviour of soft tissues with focussing on the in-vivo experimental setups. We will thoroughly review the available techniques by classifying them to four groups; elastography, indentation, aspiration and grasping techniques. The evolutions, advantages and limitations of each technique will be presented by a historical review. At the end, a discussion is given with the aim of summarising the proposed points and predicting the future of techniques utilised in extracting data related to force-deformation behaviour.